The relation between serum vitamin D levels, viral infections and severity of attacks in children with recurrent wheezing - Eroglu, Cemal (Allergol Immunopathol (Madr), 2019)
INTRODUCTION AND OBJECTIVES: Vitamin D deficiency is associated with increased susceptibility to infections and wheezing. We aimed to evaluate the relation between vitamin D levels, viral infections and severity of attacks in children with recurrent wheezing. MATERIALS AND METHODS: A total of 52 patients who applied with wheezing, at the ages of 12–60 months with a history of three or more wheezing attacks in the last year and 54 healthy children were included. Sociodemographic data, risk factors for recurrent wheezing, and the severity of the wheezing attacks were recorded. 25(OH)D3, calcium, phosphor, alkaline phosphatase and parathormone levels of all children were measured. Nasopharyngeal samples of the patients for viruses were studied by multiplex polymerase chain reaction. RESULTS: For the patient group, being breastfed for six months or less, history of cesarean section, cigarette exposure, humid home environment, and family history of allergic disease were significantly higher compared with the control group. Serum vitamin D levels in the patient group were significantly lower compared to the control group. There was no significant relationship between vitamin D levels and hospitalization, oxygen or steroid therapy. Virus was detected in 38 patients (73%). Rhinovirus (63.2%) was the most frequently detected virus. Coinfection was found in 14 (36.8%) patients. There was no statistically significant difference between detection of virus and vitamin D levels. CONCLUSIONS: Cigarette exposure, being breastfed six months or less, humid home environment, history of cesarean section, family history of allergic disease and vitamin D deficiency might be risk factors for recurrent wheezing.